Hygiene Related Risk Factors for Giardia Infection in Sukowono District, Jember, Indonesia - Selly Silfana Liensa; Wiwien Sugih Utami; Pulong Wijang Pralampita; Bagus Hermansyah (Faculty of Medicine, University of Jember, 2022)
Giardia spp. is a common cause of diarrhoeal disease in humans and is also known as a zoonotic agent in humans and animals. There are three risk factors of zoonotic Giardia, the first is individual characteristics, the second is hygiene, and the last is environmental. This study aimed to analyze the hygiene related risk factors for Giardia infection in Sukowono District, Jember. The research design was a cross-sectional study with 52 subjects from Sukowono District, Jember. The study was carried out from December 2020 to April 2021. The sampling method used purposive sampling is a non-probability sample and chi-square test for data analysis. Data was analyzed using SPSS statistics programme. P value < 0,05 was considered statistically significant.The result of microscopic examination of 52 fecal samples found 1.9% of the subjects were infected with Giardia spp. There was no association between hygiene behavior factors with Giardia spp. in Sukowono District, Jember (p>0.05). Data suggest that risk factors may not contribute to Giardia spp. infection. Based on these findings, need to do further research about hygiene related risk factors for Giardia spp. infection in Jember especially Sukowono District. Keywords: Hygiene factor, Giardia infection, zoonosis